Roles of Agricultural Marketing Institutions in Mizoram - Zonuntluanga, R. (Indian Journal of Marketing, 2007)
Mizoram is an agricultural State where the cultivators constituted 53.91 per cent of the total main workers in 2001. The total income of the State during 1998-99 was estimated at Rs.1, 13,896.00 lakhs of which 29.39 per cent came from the agriculture and allied industries, while the figure for India stood at 26.03 per cent. In the absence of development in such other sectors as agro-based industries and other allied manufacturing agencies and tertiary sector, agriculture still continues to be the main occupation of the people of Mizoram. Jhum or Shifting Cultivation continues to be the principal and prevalent method of cultivation. In this scenario, amongst others, Ginger, Chillies and Squash (chow chow) form the major list of outputs marketed. The other being Sesame, Pineapple, Oranges, Hatkora and Passion fruits. As of now, when we speak of agricultural marketing, marketing of these 8 important commodities assume an added importance in the State. For, they are the only farm produces of the State that the internal markets could not absorbed at present. Since ginger and chillies are the most important traded commodities outside the state, they have been selected for the study. The present discourse is an attempt to analyse how agricultural marketing is conducted in Mizoram; and the roles played by marketing institutions were also touched upon. Originally the survey was conducted in connection with my Ph.D thesis on Marketing of Agricultural Produce in Mizoram under Mizoram Universiry. I obtained the degree in 2004 The present study is based upon the published literatures on the subject, secondary data collected from various sources.